A prospective study to compare the effectiveness of saline dressing versus povidone iodine dressing in chronic diabetic wound healing: study from a tertiary hospital in south India - Gopi, Ellikunnel Vithon; Basava, Amrut H.; Matad, Siddharth (International Surgery Journal, 2017)
Background: Saline dressings and povidone iodine dressings have been traditionally used for the management of chronic diabetic wounds Methods: Subjects attending diabetic wound clinic and surgery outpatient department/ casualty of Government Medical College and Hospital, Kozhikode, Kerala, India were divided into two groups by consecutive sampling i.e., Povidone iodine and Saline dressing group. Regular occlusive dressing was done for 6 weeks of follow-up period. Results: 3 out of 20 subjects in Saline treated group achieved complete healing by 6 weeks as compared to 1 out of 20 subjects in Povidone iodine treated group. There was a significant decrease in the wound surface area at 6th week in Saline dressing group in comparison to the povidone iodine group at P = 0.03 (<0.05) level of significance. Conclusions: Saline dressing is more effective in achieving healing in chronic diabetic wounds as compared to Povidone iodine dressing.